2013
DOI: 10.1186/1471-2431-13-179
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus and granulomatous lymphadenopathy

Abstract: BackgroundSystemic lupus erythematosus (SLE) is known to present with a wide variety of clinical manifestations. Lymphadenopathy is frequently observed in children with SLE and may occasionally be the presenting feature. SLE presenting with granulomatous changes in lymph node biopsy is rare. These features may also cause diagnostic confusion with other causes of granulomatous lymphadenopathy.Case presentationWe report 12 year-old female who presented with generalized lymphadenopathy associated with intermitten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 20 publications
0
16
1
1
Order By: Relevance
“…In addition, abdominal lymph node enlargement could be the only imaging manifestation in patients with AILD [14]. It was reported that lymph nodes in patients with CTD were not limited to the body surface, but were in fact also distributed in the abdominal cavity [22]. However, in our study, abdominal lymph nodes tended to be most prevalent in patients with AILD (69.6%), significantly higher than in CTD patients (29.6%).…”
Section: Discussioncontrasting
confidence: 65%
“…In addition, abdominal lymph node enlargement could be the only imaging manifestation in patients with AILD [14]. It was reported that lymph nodes in patients with CTD were not limited to the body surface, but were in fact also distributed in the abdominal cavity [22]. However, in our study, abdominal lymph nodes tended to be most prevalent in patients with AILD (69.6%), significantly higher than in CTD patients (29.6%).…”
Section: Discussioncontrasting
confidence: 65%
“…Although SLE is a multisystemic autoimmune disease that courses with tissue damage arising from the immune system, the beginning with lymph node involvement is very rarely seen (1,(4)(5)(6) . The etiology is not known exactly.…”
Section: Discussionmentioning
confidence: 99%
“…SLE, which is a multisystemic disease, might be observed to show different clinical findings depending on the organ involvement. In a previous study, the initial symptoms of SLE patients were reported to be fever (67%), arthritis (61%), skin lesions (59%), and lymphadenopathy (LAP) (27.1%), another study reported that the most frequently seen initial symptoms were serositis, polyarthritis, and malar rash (4,5) .…”
Section: Intoductionmentioning
confidence: 99%
“…4 It is estimated 13-45% children with SLE are having lymphadenopathy. 5 Neither American College of Rheumatology criteria (ACR criteria) nor the Systemic Lupus International Collaborating Clinics (SLICC) criteria does not include lymphadenopathy as a diagnostic criterion. Lymphadenopathy is commonly seeing in children with SLE, but it is being a presenting feature is less frequent.…”
Section: Discussionmentioning
confidence: 99%